Hydrogen technologies and developments in Japan. Issue 2 (8th May 2019) - Iida, Shigeki; Sakata, Ko
Abstract: The successful development of hydrogen-energy technologies has several advantages and benefits. Hydrogen-energy development could prevent global warming as well as ensure energy security for countries without adequate energy resources. The successful development of hydrogen would provide energy for transportation and electric power. It is a unique energy carrier, as it can be produced from various energy sources such as wind, fossil fuels and biomass and, when it is combusted, it emits no CO2 emissions. The other advantage is the wide distribution of resources globally that can be used to produce hydrogen. In Japan, the Ministry of Economy, Trade and Industry (METI) published a 'Strategic Roadmap for Hydrogen and Fuel Cells' in 2014, with a revised update published in March 2016. The goal of the roadmap is to achieve a hydrogen society. The roadmap aims to resolve technical problems and secure economic efficiency. The roadmap has been organized into the following three phases: Phase 1—Installation of fuel cells; Phase 2—Hydrogen power plant/mass supply chain; Phase 3—CO2 -free hydrogen. This paper reports on the current status of fuel cells and fuel-cell vehicles in Japan and gives a description and status of the R&D programmes along with the results of global energy model study towards 2050.